Gender and the time cost of peer review - Diane Alexander; Olga Gorelkina; Erin Hengel; Richard S. J. Tol (Tinbergen Institute, 2023)
In this paper, we investigate one factor that can directly contribute to-as well as indirectly shed light on the other causes of-the gender gap in academic publishing: length of peer review. Using detailed administrative data from an economics field journal, we find that, conditional on manuscript quality, referees spend longer reviewing female-authored papers, are slower to recommend accepting them, manuscripts by women go through more rounds of review and their authors spend longer revising them. Less disaggregated data from 32 economics and finance journals corroborate these results. We conclude by showing that all gender gaps decline-and eventually disappear-as the same referee reviews more papers. This pattern suggests novice referees initially statistically discriminate against female authors, but are less likely to do so as their information about and confidence in the peer review process improves. More generally, they also suggest that women may be particularly disadvantaged when evaluators are less familiar with the objectives and parameters of an assessment framework.
Keywords: A11; D8; J16; J24; J7; 330; Gender Inequality; Statistical Discrimination; Research Productivity; Peer Review